Comparative phytochemical and pharmacological analysis of two cultivars of Annona squamosa L. cultivated in Egypt - Safaa Yassin; Samah M. Elsohafy; Amr El-Hawiet; Maged S. Abdel-Kader; Doaa A. Ghareeb; Fikria A. Darwish; Masouda E. Amer (npj Science of Food)
Abstract This study compared two Annona squamosa L. cultivars, Abdelrazik (Annona A.) and Balady (Annona B.), in terms of their chemical profile, in vitro cytotoxicity against HCT-116 and A549 cell lines, and total acetogenin. In addition, the two cultivars pulp were compared regarding carbohydrates and magnesium ions content and immunomodulating activity. The two cultivars were also differentiated genetically by DNA barcoding using the universal primer matK and the specific primer Annona squamosa matK. The results showed that Annona A. seeds had higher acetogenin content and exhibited more potent cytotoxic activity against the two cell lines. In contrast, Annona B. pulp had higher carbohydrate content and lower magnesium ions content. The splenic lymphocyte proliferation assay revealed that Annona A. pulp extract was slightly more active as an immunostimulant. The specific primer used for DNA barcoding was more effective for species identification, while the universal primer was better for cultivar differentiation. Overall, our findings indicate the potential for using active compounds of Annona squamosa L. cultivars to develop new therapeutic agents for cancer therapy and immune enhancement.